Comparing human and macaque placental transcriptomes to disentangle preterm birth pathology from gestational age effects. (May 2016) - Eidem, Haley R.; Rinker, David C.; Ackerman, William E.; Buhimschi, Irina A.; Buhimschi, Catalin S.; Dunn-Fletcher, Caitlin; Kallapur, Suhas G.; Pavličev, Mihaela; Muglia, Louis J.; Abbot, Patrick; Rokas, Antonis
Abstract: Introduction: A major issue in the transcriptomic study of spontaneous preterm birth (sPTB) in humans is the inability to collect healthy control tissue at the same gestational age (GA) to compare with pathologic preterm tissue. Thus, gene expression differences identified after the standard comparison of sPTB and term tissues necessarily reflect differences in both sPTB pathology and GA. One potential solution is to use GA-matched controls from a closely related species to tease apart genes that are dysregulated during sPTB from genes that are expressed differently as a result of GA effects. Methods: To disentangle genes whose expression levels are associated with sPTB pathology from those linked to GA, we compared RNA sequencing data from human preterm placentas, human term placentas, and rhesus macaque placentas at 80% completed gestation (serving as healthy non-human primate GA-matched controls). We first compared sPTB and term human placental transcriptomes to identify significantly differentially expressed genes. We then overlaid the results of the comparison between human sPTB and macaque placental transcriptomes to identify sPTB-specific candidates. Finally, we overlaid the results of the comparison between human term and macaque placental transcriptomes to identify GA-specific candidates. Results: Examination of relative expression for all human genes with macaque orthologs identified 267 candidate genes that were significantly differentially expressed between preterm and term human placentas. 29 genes were identified as sPTB-specific candidates and 37 as GA-specific candidates. Altogether, the 267 differentially expressed genes were significantly enriched for a variety of developmental, metabolic, reproductive, immune, and inflammatory functions. Although there were no notable differences between the functions of the 29 sPTB-specific and 37 GA-specific candidate genes, many of these candidates have been previously shown to be dysregulated in diverse pregnancy-associated pathologies. Discussion: By comparing human sPTB and term transcriptomes with GA-matched control transcriptomes from a closely related species, this study disentangled the confounding effects of sPTB pathology and GA, leading to the identification of 29 promising sPTB-specific candidate genes and 37 genes potentially related to GA effects. The apparent similarity in functions of the sPTB and GA candidates may suggest that the effects of sPTB and GA do not correspond to biologically distinct processes. Alternatively, it may reflect the poor state of knowledge of the transcriptional landscape underlying placental development and disease. Highlights: Ethical issues prevent collection of appropriate control tissues in studies of human spontaneous preterm birth (sPTB). Gestational age (GA) controls from closely related species allow for the identification of human sPTB- and GA-specific genes. We compared transcriptomes from human preterm, human term, and healthy GA-matched macaque placentas. Our novel, comparative approach identified 29 sPTB- and 37 GA-specific genes as promising candidates for future research.